Association Between the Coronary Sinus Ostial Size and Atrioventricular Nodal Reentrant Tachycardia in Patients With Pulmonary Arterial Hypertension - Ding, Lei; Weng, Sixian; Zhai, Zhengqin; Zhou, Bin; Qi, Yingjie; Yu, Fengyuan; Zhang, Hongda; Zhang, Shu; Tang, Min (Frontiers in Physiology, 2022)
Aims: The incidence of atrioventricular nodal reentrant tachycardia (AVNRT) is higher in pulmonary arterial hypertension (PAH) patients than in the general population. AVNRT is reportedly associated with a larger coronary sinus (CS) ostium (CSo). However, the correlation between AVNRT and CSo size in PAH patients is poorly investigated. We aimed to investigate the impact of CSo size on AVNRT and identify its risk factors in PAH. Methods and results: Of 102 PAH patients with catheter ablation of supraventricular tachycardia (SVT), twelve with a confirmed AVNRT diagnosis who underwent computed tomographic angiography were retrospectively enrolled as the study group. The control group (PAH without SVT, n=24) was matched for sex and BMI at a 2:1 ratio. All baseline and imaging data were collected. Mean pulmonary artery pressure was not significantly different between the two groups (65.3 ± 16.8 vs. 64.5 ± 17.6 mmHg, P = 0.328). PAH patients with AVNRT were older (45.9±14.8 vs. 32.1±7.6 years, P = 0.025), had a larger right atrial volume (224.4 ± 129.6 vs. 165.3 ± 71.7 cm3, P = 0.044), larger CSo in the left anterior oblique (LAO) plane (18.6 ± 3.3 vs. 14.8 ± 4.0 mm, P = 0.011), and larger CSo surface area (2.08 ± 1.35 vs. 1.45 ± 0.73 cm2, P = 0.039) and were more likely to have a windsock-shape CS (75% vs. 16.7%, P = 0.001) than those without AVNRT. A linear correlation was shown between CSo diameter in the LAO-plane and the atrial fractionation of the ablation target for AVNRT (R2 = 0.622, P = 0.012). Conclusions: Anatomical dilation of the CSo is a risk factor for AVNRT development in patients with PAH.